1985
DOI: 10.1038/bjc.1985.34
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal analysis of neuroblastoma

Abstract: Summary Ten children with abdominal neuroblastoma were included in the study. Biopsies from the neuroblastomas were taken during surgical operations, nine from the primary tumours and one from a metastasis. Histopathology was done for diagnosis. Chromosomal cultures of neuroblastoma cells and peripheral blood lymphocytes were performed.The peripheral blood lymphocytes revealed normal chromosomal complements. The 10 tumours were in the peridiploid range with random gains or losses of chromosomes. Deletion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This chromosomal region has been implicated in the development of neuroblastoma. Tumor cells derived from 70 % of patients with neuroblastoma exhibit a deletion of part of the short arm of chromosome 1 [39]. Molecular analysis of a number of neuroblastoma cell lines indicates that the deletions cluster at position 1p32 [40].…”
Section: Discussionmentioning
confidence: 99%
“…This chromosomal region has been implicated in the development of neuroblastoma. Tumor cells derived from 70 % of patients with neuroblastoma exhibit a deletion of part of the short arm of chromosome 1 [39]. Molecular analysis of a number of neuroblastoma cell lines indicates that the deletions cluster at position 1p32 [40].…”
Section: Discussionmentioning
confidence: 99%
“…The short-arm deletions usually involved the part distal to 1p32, although reports about the affected region on 1p were not always consistent. Most of the early studies showed long terminal deletions (Brodeur et al, 1981;Gilbert et al, 1982;Hafez et al, 1985), whereas recent investigations could restrict the region of interest to 1p36 (Fong et al, 1989;Weith et al 1989;Cheng et al, 1995;White et al, 1995;Bauer et al, 2001;Maris et al, 2001). Some authors have proposed two different loci on 1p containing at least two tumor-suppressor genes (Schleiermacher et al, 1994;Takeda et al, 1994;Mora et al, 2000), with the second more proximal one showing less prognostic relevance compared to the distal 1p36 (Mora et al, 2000).…”
Section: Introductionmentioning
confidence: 93%
“…1970). Cells from at least 70% of these tumors exhibit a loss of the distal portion of the short arm of chromosome 1 (Brodcur et al" 1981: Haag ct al" 1981Gilbert et al" 1982;Hafez, et al" 1985). Other chromosomal abnormalities associated with this tumor include double minute chromosomes (DMs) and homoge neously staining regions (HSRs) that are believed to represent the amplification of M YCN and its surrounding genes (Montgomery etal.. 1983: Kohletal.. 1984Hafez etal.. 1985: Shiloh et al.…”
mentioning
confidence: 99%